Pengaruh Performa Pasangan terhadap Emosi pada Atlet Bulutangkis Ganda Jepara - Tamtomo, Gelar Tabernakel Gen; Kusuma, Donny Wira Yudha (Universitas Negeri Semarang, 2023)
The purpose of this study was to analyze and determine impact of partner performance on emotions in athletes doubles badminton Jepara. The method used is correlation through a quantitative approach. The research instrument used the Sport Emotion Questionnaire Test and the Group Environment Questionnaire. The data obtained were analyzed using descriptive percentages, validity and reliability tests, product moment correlation tests, and simple regression tests. The results of the study, (1) the performance condition of doubles badminton athletes in Jepara is in the moderate category, with a percentage level reaching 53.65%, (2) the emotional condition of doubles badminton athletes in Jepara is in the stable category, with a percentage level reaching 74.53%. , (3) the value of Sig. (2-tailed) product moment correlation <0.05 with r count > r table value, and Sig. (2-tailed) F test <0.05 with a coefficient of determination (R2) of 0.462, meaning that there is a relationship and influence of partner performance on the emotions of doubles badminton athletes in Jepara with an effect of 46.2%. In conclusion, there is an impact of partner performance on emotions in athletes doubles badminton Jepara